A micromagnetic study: lateral size dependence of the macroscopic properties of rectangular parallelepiped Cobalt-ferrite nanoferromagnetic - Nur Aji Wibowo; Susatyo Pranoto; Cucun Alep Riyanto; Andreas Setiawan (Journal of Physics: Theories and Applications, 2020)
The purpose of this study is to provide systematic information through micromagnetic simulations related to the impact of particle size on the magnetic characteristics of Cobalt-ferrite MNP. The micromagnetic computations performed were based on LLG equation. The MNPs sample was simulated in the form of a rectangular parallelepiped with a thickness of 20 nm and square surface with lateral length varies from 10 to 80 nm at an interval of 10 nm. The results of this study indicate that the size changes in Cobalt-ferrite MNP have a significant impact on various magnetic properties, such as the magnitude of the barrier energy, coercive and nucleation fields, magnetization rate, magnetization curve profile, and magnetization mode.Cobalt-ferrite MNP with a size of 10 nm shows a single domain with a relatively short magnetization reversal time and high coercive field.